1999
DOI: 10.1094/phyto.1999.89.6.518
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Rust Resistance Gene Lr34 Associated with Nonsuppression of Stem Rust Resistance in the Wheat Cultivar Canthatch

Abstract: The common wheat cultivar Thatcher and the backcross derivative Canthatch are moderately or fully susceptible to several races of stem rust because of a suppressor on chromosome 7DL that inhibits the expression of the relevant resistance gene(s). The incorporation of leaf rust resistance gene Lr34 into 'Thatcher' is known to enhance stem rust resistance. The effect of this gene in a 'Canthatch' background and its relationship with the 7DL suppressor were determined by replacing chromosome 7D of 'Canthatch' wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Liu and Kolmer (1998) reported the association of Lr34 and stem rust resistance in Canadian wheat cultivar Pasqua. Kerber and Aung (1999) reported that ''in Canthatch background, Lr34 inactivates the suppressor on the chromosome arm 7DL and thereby permits the expression of resistance''. These workers were unable to associate the moderate level of stem rust resistance with Lr34, presumably due to the activation of highly effective genes in Thatcher and Canthatch.…”
Section: Discussionmentioning
confidence: 99%
“…Liu and Kolmer (1998) reported the association of Lr34 and stem rust resistance in Canadian wheat cultivar Pasqua. Kerber and Aung (1999) reported that ''in Canthatch background, Lr34 inactivates the suppressor on the chromosome arm 7DL and thereby permits the expression of resistance''. These workers were unable to associate the moderate level of stem rust resistance with Lr34, presumably due to the activation of highly effective genes in Thatcher and Canthatch.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which Lr34 mediates the enhancement of stem rust resistance in Thatcher is not well understood. Lr34 appears to inhibit a suppressor of stem rust resistance on chromosome 7D (Kerber and Aung 1999). This suppressor is commonly found in hexaploid wheat and is present in the donor of the D genome, Triticum tauschii (Kerber 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Dyck (1987) mapped Lr34 to chromosome 7D and found that Thatcher backcross lines with Lr34 had superior stem rust resistance compared to the recurrent parent Thatcher. Gene Lr34 may counter the eVect of a stem rust resistance suppressor gene that is present on chromosome 7D in many common hexaploid wheat cultivars (Kerber and Aung 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is still not clear, however, whether Ltn is pleiotropic to or tightly linked with Lr34. In addition, the Ltn/Lr34 chromosomal segment also confers a durable resistance to stripe (yellow) rust, Yr18 (Singh 1992b), stem rust (Liu and Kolmer 1998), as well as tolerance against the barley yellow dwarf virus, Bdv1 (Singh 1993;Ayala et al 2002) and inactivates a stem rust resistance suppressor (Kerber and Aung 1999). Thus, Ltn/Lr34 is unique and a very valuable source of disease resistance in wheat breeding.…”
Section: Introductionmentioning
confidence: 99%